2007
DOI: 10.1007/s00044-007-9040-9
|View full text |Cite
|
Sign up to set email alerts
|

Production, optimization and purification of an antifungal compound from Streptomyces capoamus MTCC 8123

Abstract: A microbial isolate showed strong antibacterial and antifungal activity against various multidrug-resistant test organisms. Based on physiological and biochemical characteristics and 16S ribosomal RNA sequence homology studies, it was found to be similar to Streptomyces capoamus (gene sequence similarity 98%). The antifungal metabolite was produced majorly intracellularly. The active metabolite was extracted and purified by gel filtration chromatography and highperformance liquid chromatography (HPLC). Partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Actinomycete cell metabolism under conditions of nutritional excess is directed towards the generation of cell mass rather than the production of secondary metabolites, and when depletion of key nutrients occurs, it shifts the cell cycle to the stationary phase and signals the transition from primary to secondary metabolism in which these bioactive metabolites are produced (Abanat et al 1999l;Abd-Allah & El-Mehalawy 2002). In the present investigation, the time course of fermentation of Streptomyces rochei (MTTC 10109) showed mycelial growth up to 72 h followed by a stationary phase; antimicrobial metabolite production was detected after 48 h incubation, and reached optimum yields in the late exponential and stationary phase after 120 h incubation, indicating mainly secondary metabolism (Demain & Fang 1995;Bibb 1996;Vineeta et al 2008).…”
Section: Discussionmentioning
confidence: 57%
“…Actinomycete cell metabolism under conditions of nutritional excess is directed towards the generation of cell mass rather than the production of secondary metabolites, and when depletion of key nutrients occurs, it shifts the cell cycle to the stationary phase and signals the transition from primary to secondary metabolism in which these bioactive metabolites are produced (Abanat et al 1999l;Abd-Allah & El-Mehalawy 2002). In the present investigation, the time course of fermentation of Streptomyces rochei (MTTC 10109) showed mycelial growth up to 72 h followed by a stationary phase; antimicrobial metabolite production was detected after 48 h incubation, and reached optimum yields in the late exponential and stationary phase after 120 h incubation, indicating mainly secondary metabolism (Demain & Fang 1995;Bibb 1996;Vineeta et al 2008).…”
Section: Discussionmentioning
confidence: 57%
“…Natural products have long been used as templates for the design of new lead compounds which may be useful against infectious diseases, such as blactams, tetracyclins, echinocandins, and macrolydes (Newman and Cragg, 2007). In this context, several metabolites of different structural patterns have proven active against microorganisms, and screening of extracts is a valid strategy being exploited to discover novel antimicrobial agents (Acharya et al, 2008;Singh et al, 2008;Tripathi et al, 2004;Viswanathan et al, 2004;Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has previously reported that during the production of antifungal compound from Streptomyces capoamus , removal of soybean meal or glycerol or NaCl from the fermentation medium decreased the yield by 20–40% (Singh et al, 2008). …”
Section: Media Optimization Strategiesmentioning
confidence: 99%